Etrasimod in Treatment of Ulcerative Colitis: A Comprehensive Review - Buldukoglu, Osman Cagin; Erzin, Yusuf; Cekin, Ayhan Hilmi; Danese, Silvio (Turkish Journal of Gastroenterology, 2025)
Ulcerative colitis (UC) is a chronic, inflammatory disease of the colon. The unpredictable, systemic, and debilitating nature of UC puts disease management and patient monitoring at a pivotal point. Despite substantial development in pharmacotherapies for UC in recent years, a significant proportion of patients either fail to respond to treatment or lose their response over the course of the disease. The backbone of disease management in UC is 5-aminosalicylic acid (5-ASA), but patients unresponsive to 5-ASA or with severe disease require advanced therapies including tumor necrosis factor-alpha inhibitors (TNFi), anti-integrins, anti-interleukins and small molecule therapy, Janus kinase (JAK) inhibitors, and S1PR modulators. This review will briefly overview the current state of medical therapeu tic options in UC, with further detailing the molecular and clinical aspects of Etrasimod, a sphingosine-1-phosphate receptor (S1PR) modulator. Cite this article as: Buldukoglu OC, Erzin Y, Cekin AH, Danese S. Etrasimod in treatment of ulcerative colitis: A comprehensive review. Turk J Gastroenterol. 2025;36(6):336-342.